Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 6 Rational Exponents and Radical Functions - Cumulative Review Chapters 1-6 - Page 474: 23



Work Step by Step

If we add three times the first equation to the second equation, we get: $13x=-13\\x=-1$ Now plugging this into the first equation: $3(-1)-y=-9\\-3-y=-9\\-y=-6\\y=6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.